2021
DOI: 10.1111/jocn.15913
|View full text |Cite
|
Sign up to set email alerts
|

Feeling like the sky is falling down: Experiences of parents of adolescents diagnosed with cancer in one‐child families in China – A qualitative study

Abstract: Background As a result of the one‐child policy of 1979, today there are numerous one‐child families with adolescents in Mainland China. Little is known about the experiences of parents of such adolescents diagnosed with cancer. Objectives This study explored the experiences of parents whose adolescent child was diagnosed with cancer in one‐child families in China. Methods A qualitative methodology based on hermeneutic phenomenology was employed. The participants were parents of adolescent cancer patients in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 56 publications
0
18
0
2
Order By: Relevance
“…We included sixteen studies in this systematic review. Of these, seven studies were focused on the psychological impact of cancer on caregivers of AYA CCS [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and nine studies on caregivers of AYA with cancer [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…We included sixteen studies in this systematic review. Of these, seven studies were focused on the psychological impact of cancer on caregivers of AYA CCS [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and nine studies on caregivers of AYA with cancer [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Al comparar los hallazgos con la literatura actual, se observó que hay una concordancia con que el diagnóstico inesperado de cáncer en un hijo impactó fuertemente a los padres. Estudios cualitativos muestran una experiencia global similar; investigaciones de distintos países encontraron que la situación fue como sentir que el cielo colapsa, (16) como un desastre terrible (22) y como una de sus experiencias más difíciles y dolorosas. (23,24) Dentro de los hallazgos reportados en este estudio destaca que la visión de la propia corporalidad y del espacio interno de madres y padres fue olvidado en pos del cuidado del niño/a, lo cual se puede vincular a la evidencia actual que muestra que el cuidado de un niño con cáncer se asocia a mayores síntomas depresivos en padres y madres, (25,26) síntomas de estrés postraumático (27) e incluso que la carga de cuidado impacta su calidad de vida.…”
Section: Discussionunclassified
“…Para responder a esta pregunta se realizó una investigación basada en la fenomenología experiencial o fenomenología de la práctica de Van Manen. Este enfoque de investigación ha sido utilizado por algunos autores para comprender la experiencia de personas que viven situaciones de salud grave como el cáncer (15)(16)(17)(18) y es aplicable al objetivo del presente proyecto porque permite describir minuciosamente y comprender de mejor manera el mundo que madres y padres vivencian en la experiencia de hospitalización de sus hijos(as) a causa del cáncer.…”
unclassified
“…Collectively, this study observed that relatives with chronic disease were associated with individuals’ suicidal ideation firstly, which was consistent with results concluded by previous research. Regarding this, relatives’ physical health was determined to be a risk factor affecting suicidal ideation in past studies [ 48 , 49 ]. The reasons for this relevance cause concern and explorations were presented in numerous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning physical health, previous literature revealed that severe illness or death of fathers and spouses’ cancer were associated with their FM’s mental status [ 48 ]. In China, a study revealed that kids with diagnosed cancer would cause psychological injury to parents, such as desperation and suicidal ideation [ 49 ]. In addition to the influence of physical illness, family members suffering from mental illness, such as spouses, parents, and others, may affect the mental status and suicidal ideation of adults [ 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%